Innovation in surgical curriculum teaching methodology: vertical integration revisited - Kaur, Manmeet; Mathur, Alok V. (International Surgery Journal, 2018)
Background: Vertical integration refers to the learning of basic sciences in the context of clinical and professional practice. It has been seen to be more meaningful and relevant to students. Objective of the study was to design and implement a vertically integrated module for teaching thyroid surgery in a modified way to the MBBS students at Shri Guru Ram Rai Institute of Health and Medical Sciences, Dehradun. Methods: Study was conducted in the Department of Surgery. A total of 200 students (50 each from four batches of MBBS at SGRRIH and MS, Dehradun), were enrolled to the same teaching modalities, materials and evaluation tools. At the end of the teaching lectures, a feedback questionnaire was filled by the students. Thirty MCQs were given both in pre and post session and results compared. Results: Feedback from students was very encouraging. In MCQ assessment, pre-session only 40% secured marks in the pass range, where as in the post session questionnaire, 89% passed and 11% failed only marginally. Conclusions: Vertical integration needs additional effort, time and teamwork from faculty members of different departments. It is useful to have smaller topics of clinical significance covered in one session rather than attempting to cover a broad area, as this often results in a loss of interest. Preparation of curriculum together by basic, preclinical and clinical teachers can lead to more relevant teaching.